1993
DOI: 10.2307/2111383
|View full text |Cite
|
Sign up to set email alerts
|

Completing the Single European Market: An Analysis of the Impact on the Member States

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…1 Recent work has suggested that the issue of economic benefits associated with EU membership is not only crucial for understanding the dynamics of integration and public support for it, but that it is also more complex than is often assumed. Thus, Smith and Wanke (1993) have pointed out that while the EU as a whole may benefit from the implementation of the SEA, the 1992 program, and the Maastricht treaty (Cecchini 1988), different countries can be expected to be differentially successful at dealing with greater economic integration (see also Garrett 1992). The same can be said of individuals (Gabel and Palmer 1995).…”
Section: Differences In Support and The Cost-benefit Calculusmentioning
confidence: 99%
“…1 Recent work has suggested that the issue of economic benefits associated with EU membership is not only crucial for understanding the dynamics of integration and public support for it, but that it is also more complex than is often assumed. Thus, Smith and Wanke (1993) have pointed out that while the EU as a whole may benefit from the implementation of the SEA, the 1992 program, and the Maastricht treaty (Cecchini 1988), different countries can be expected to be differentially successful at dealing with greater economic integration (see also Garrett 1992). The same can be said of individuals (Gabel and Palmer 1995).…”
Section: Differences In Support and The Cost-benefit Calculusmentioning
confidence: 99%
“…12 At the aggregate level of public opinion, nationality or national cultural heritage is important through longestablished political traditions or national specific cultural legacies (Gabel 1998a;Bosch and Newton 1995;Eichenberg and Dalton 1993;Smith and Wanke 1993). Unfortunately, the notion of 'national context' does little to pull back the curtain on underlying complexities; although, one author has linked aggregate support with significant moments in EU history, particularly the emergence of treaties (Çíftçí 2005) thereby implying a relationship between the EU policy process and support.…”
Section: National Vs European Identitiesmentioning
confidence: 99%
“…A distinct facet of the sociotropic approach is the assessment of being a net beneficiary of the net transfers from the EU to the nation (Anderson and Reichert 1995;Gabel 1998a;Carrubba 1997Carrubba , 2001Gabel and Palmer 1995;Smith and Wanke 1993). While economic in nature, the underlying assumption is that further EU expansion implies continued market liberalization.…”
mentioning
confidence: 99%
“…Appealing to the outright 'costs of non-Europe', many found favorable national-level economic evaluations to be the source (Anderson and Kaltenthaler 1996;Eichenberg and Dalton 1993) and others addressed regional and sectoral economic variation (Smith and Wanke 1993).…”
Section: Instrumental Self-interestmentioning
confidence: 99%
“…A distinct facet of the sociotropic approach is the assessment of being a net beneficiary of the net transfers from the EU to the nation (Anderson and Reichert 1996;Gabel 1998a;Carrubba 1997Carrubba , 2001Gabel and Palmer 1995;Smith and Wanke 1993). While economic in nature, the underlying assumption is that further EU expansion implies continued market liberalization.…”
Section: Instrumental Self-interestmentioning
confidence: 99%